Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

When f(x) = 10x^2-5x-6, evaluate f(-2) what is answer

Sagot :

Answer:

f = -5 + -6x-1 + 10x

Step-by-step explanation:

Simplifying

f(x) = 10x2 + -5x + -6

Multiply f * x

fx = 10x2 + -5x + -6

Reorder the terms:

fx = -6 + -5x + 10x2

Solving

fx = -6 + -5x + 10x2

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.

f = -6x-1 + -5 + 10x

Simplifying

f = -6x-1 + -5 + 10x